Multimodal subtypes identified in Alzheimer’s Disease Neuroimaging Initiative participants by missing-data-enabled subtype and stage inference - Estarellas, Mar; Oxtoby, Neil P; Schott, Jonathan M; Alexander, Daniel C; Young, Alexandra L (Brain communications, 2024)
Abstract Alzheimer’s disease is a highly heterogeneous disease in which different biomarkers are dynamic over different windows of the decades-long pathophysiological processes, and potentially have distinct involvement in different subgroups. Subtype and Stage Inference is an unsupervised learning algorithm that disentangles the phenotypic heterogeneity and temporal progression of disease biomarkers, providing disease insight and quantitative estimates of individual subtype and stage. However, a key limitation of Subtype and Stage Inference is that it requires a complete set of biomarkers for each subject, reducing the number of datapoints available for model fitting and limiting applications of Subtype and Stage Inference to modalities that are widely collected, e.g. volumetric biomarkers derived from structural MRI. In this study, we adapted the Subtype and Stage Inference algorithm to handle missing data, enabling the application of Subtype and Stage Inference to multimodal data (magnetic resonance imaging, positron emission tomography, cerebrospinal fluid and cognitive tests) from 789 participants in the Alzheimer’s Disease Neuroimaging Initiative. Missing-data Subtype and Stage Inference identified five subtypes having distinct progression patterns, which we describe by the earliest unique abnormality as ‘Typical AD with Early Tau’, ‘Typical AD with Late Tau’, ‘Cortical’, ‘Cognitive’ and ‘Subcortical’. These new multimodal subtypes were differentially associated with age, years of education, Apolipoprotein E (APOE4) status, white matter hyperintensity burden and the rate of conversion from mild cognitive impairment to Alzheimer’s disease, with the ‘Cognitive’ subtype showing the fastest clinical progression, and the ‘Subcortical’ subtype the slowest. Overall, we demonstrate that missing-data Subtype and Stage Inference reveals a finer landscape of Alzheimer’s disease subtypes, each of which are associated with different risk factors. Missing-data Subtype and Stage Inference has broad utility, enabling the prediction of progression in a much wider set of individuals, rather than being restricted to those with complete data. Estarellas et al. report that an adapted Subtype and Stage Inference algorithm accommodates missing data in multimodal Alzheimer’s disease studies. They identified five distinct subtypes, each associated with different risk factors, revealing new insights into the disease’s landscape and progression. Graphical Abstract Graphical Abstract